MENINGKATKAN KETERAMPILAN BERBICARA DENGAN METODE PAIRED STORY TELLING (BERCERITA BERPASANGAN) PADA SISWA KELAS IV DI SDN 4 CAKRANEGARA TAHUN PELAJARAN 2015/2016 - Mardiana Mardiana; Muhammad Tahir; I Nyoman Sudika (Indonesian Publication Center, 2020)
This Classroom Action Research aims to increase students’ speaking skill through method Paired Story Telling at grade IV SDN 4 Cakranegara Academic Year 2015/2016. This research was conducted in two cycles. Data collecting Method used were observation, test and documentation whereas, method of data analysis were descriptive quantitaive and qualitative. Based on data analysis result held in cycle 1, classical mean score was 67 with the number of successful studens were 20 and failed students were 12. Highest score was 75 and the lowest score was 50. So that the classical successful students in cycle 1 was 62,5%. The result of reflection in cycle 1 showed that remedial action in next cycle was required. Based on analysis conducted in cycle 2, the number of successful students were 28 and failed students were 4, with the higherst score was 95 and the lowest score was 60. The classical mean score was 77 with classical successful was 87.5 %. That result showed that the application of method paired story telling could increse speaking skill of grade IV students at SDN 4 Cakranegara Academic Year 2015/2016.